1995 Roussel Lecture. Management of adenocarcinoma of the head of the pancreas: 10 questions for the 1990s - Taylor, Bryce (Canadian Medical Association, 1996)
Carcinoma of the head of the pancreas is a lethal condition because it presents clinically late in the disease and because of its unfavourable biologic course. Surgical approaches have become progressively more aggressive in recent years, without a significant increase in long-term survival. Controversy persists as to the appropiate surgical procedure for this disease, nonoperative or operative palliation, and future prospects for management. This review considers questions often posed by clinicians and offers answers based on a literature review and the experience of the hepatobiliary service at the Toronto Hospital, Toronto General Division.